Cytidine Triphosphate Synthase Four From Arabidopsis thaliana Attenuates Drought Stress Effects - Krämer, Moritz; Dörfer, Eva; Hickl, Daniel; Bellin, Leo; Scherer, Vanessa; Möhlmann, Torsten (Frontiers in Plant Science, 2022)
Cytidine triphosphate synthase (CTPS) catalyzes the final step in pyrimidine de novo synthesis. In Arabidopsis, this protein family consists of five members (CTPS1–5), and all of them localize to the cytosol. Specifically, CTPS4 showed a massive upregulation of transcript levels during abiotic stress, in line with increased staining of CTPS4 promoter:GUS lines in hypocotyl, root and to lesser extend leaf tissues. In a setup to study progressive drought stress, CTPS4 knockout mutants accumulated less fresh and dry weight at days 5–7 and showed impaired ability to recover from this stress after 3 days of rewatering. Surprisingly, a thorough physiological characterization of corresponding plants only revealed alterations in assimilation and accumulation of soluble sugars including those related to drought stress in the mutant. Bimolecular fluorescence complementation (BiFC) studies indicated the interaction of CTPS4 with other isoforms, possibly affecting cytoophidia (filaments formed by CTPS formation. Although the function of these structures has not been thoroughly investigated in plants, altered enzyme activity and effects on cell structure are reported in other organisms. CTPS activity is required for cell cycle progression and growth. Furthermore, drought can lead to the accumulation of reactive oxygen species (ROS) and by this, to DNA damage. We hypothesize that effects on the cell cycle or DNA repair might be relevant for the observed impaired reduced drought stress tolerance of CTPS4 mutants.